Implementasi Metode Goal-Directed Design Dalam Perancangan Antarmuka Website MDMC Kabupaten Klaten Berbasis Kebutuhan Pengguna - Adika Sri Widagdo; Fachruddin Edi Nugroho Saputro; Krisna Nuresa Qodri; Nisrina Akbar Rizky Putri; Rizal Adimas Ronaldo (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This research is driven by the need for structured information media, specifically a website, to support disaster response reporting at MDMC Klaten Regency. Previously, information remained fragmented on social media, necessitating a more comprehensive platform. This study aims to design the MDMC Klaten Regency website interface based on user needs to ensure effective information delivery. The method employed is Goal-Directed Design (GDD), consisting of Research, Modeling, Requirement, Framework, Refinement, and Support stages. Data were collected through observations, interviews, and document studies, then transformed into Volunteer and General Public personas. The result is a website interface prototype featuring report publication workflows and location mapping visualization as primary features. Usability evaluation using the System Usability Scale (SUS) instrument with 59 respondents yielded an average score of 87.97. These results place the system in the "Acceptable" category with a "Grade A" rating and an "Excellent" Adjective Rating. In conclusion, the GDD approach is effective in producing interface designs aligned with user goals, characterized by high levels of navigation ease and information clarity. This study recommends further development of map interactivity to continuously optimize the user experience.